Working Beyond 65 in Ireland - Anne Nolan; Alan Barrett (Institute of Labor Economics (IZA), 2018)
Extending working lives is often proposed as one route through which the costs associated with population ageing can be managed. In that context, understanding who currently works for longer can help policymakers to design policies to facilitate longer working. In particular, it is important to know if longer working is a choice or a necessity, where necessity arises from a lack of pension income. In this paper, we use data from the first four waves of the Irish Longitudinal Study of Ageing (TILDA), covering the period 2010-2016, to examine patterns of labour force participation among men and women aged 65+. We find that a lack of pension income is an important determinant of later-life working and that this applies for both men and women. Although older women are significantly less likely to work than older men, we find few differences in the pattern of determinants of longer working among older men and women. However, while women are significantly less likely to work than men, this effect is stronger among married women compared to single women. This suggests that older women without immediate access to family-provided financial support may need to work to support themselves. This adds to the picture of later life work being a necessity as opposed to a choice. However, an alternative explanation is that older married women may also have caring responsibilities that reduce their labour force participation.
Keywords: D14; H55; J14; J26; 330; retirement; pensions; older workers; Ireland